Delirium prevention and treatment in the emergency department (ED): a systematic review protocol. Issue 10 (6th October 2020) - Dahlstrom, Elijah Blue; Han, Jin Ho; Healy, Heather; Kennedy, Maura; Arendts, Glenn; Lee, Jacques; Carpenter, Chris; Lee, Sangil
Abstract : Introduction: Delirium is a dangerous syndrome of acute brain dysfunction that is common in the emergency department (ED), especially among the geriatric population. Most systematic reviews of interventions for delirium prevention and treatment have focused on inpatient settings. Best practices of effective delirium care in ED settings have not been established. The primary objective of this study is to identify pharmacologic and non-pharmacologic interventions as applied by physicians, nursing staff, pharmacists and other ED personnel to prevent incident delirium and to shorten the severity and duration of prevalent delirium in a geriatric population within the ED. Methods and analysis: Searches using subject headings and keywords will be conducted from database inception through June 2020 in MEDLINE, EMBASE, Web of Science, PsychINFO, CINAHL, ProQuest Dissertations and Theses Global and Cochrane CENTRAL as well as grey literature. Database searches will not be limited by date or language. Two reviewers will identify studies describing any interventions for delirium prevention and/or treatment in the ED. Disagreements will be settled by a third reviewer. Pooled data analysis will be performed where possible using Review Manager. Risk ratios and weighted difference of means will be used for incidence of delirium and other binary outcomes related to delirium, delirium severity or duration of symptoms, along with 95% CIs. Heterogeneity will be measured by calculating I 2, and a forest plot will be created. If significant heterogeneity is identified, metaregression is planned using OpenMeta to identify possible sources of heterogeneity. Ethics and dissemination: This is a systematic review of previously conducted research; accordingly, it does not constitute human subjects research needing ethics review. This review will be prepared as a manuscript and submitted for publication to a peer-reviewed journal, and the results will be presented at conferences. PROSPERO trial registration number: CRD42020169654.